Collection and transportation vehicle - Yahya, Azmi; Eltayeb Ali, Mutasim (2009)

(untitled)
The invention is a new system for infield collection and transportation of oil palm fruit branches which is capable for gathering, lifting, loading, and dumping the oil palm fresh fruit bunches. The configuration of the invention consists of the main chassis and driving unit. Various functional components of the machine were hydraulically operated through a solenoid system.